Analisis Peran Badan Kesatuan Bangsa Dan Politik Dalam Pembinaan Organisasi Kemasyarakatan Di Kabupaten Sragen - Gumelar, Rismianto; Winduro, Wirid (Solidaritas, 2024)
The Sragen Regency Government plays a role in efforts to prevent conflicts between mass organizations in its territory so that it requires the role of the National Unity and Political Agency in providing guidance to community organizations. The purpose of this study is to analyze and describe the role of the National Unity and Political Agency in fostering community organizations in Sragen Regency. This type of research uses qualitative research with a field research approach. The location of this research is at the Sragen Regency National and Political Unity Agency Office. Data collection used observation, interviews and documentation. The data analysis technique uses qualitative analysis. The results showed that the role of Kesbangpol in carrying out the facilitator function in fostering mass organizations in Sragen Regency is in providing facilities and infrastructure to mass organizations in the form of assistance for building rehabilitation as well as providing financial assistance. The role of Kesbangpol in carrying out the legislator function in fostering mass organizations in Sragen Regency is to implement Law No. 16 of 2017 and the role of Kesbangpol in carrying out the catalyst function is to provide guidance on national insight and administrative system guidance to mass organizations in Sragen Regency once a year which aims to ensure the harmony of all mass organizations can be well established. Keywords: role, coaching, community organization